Dual-functional cellulase-mediated gold nanoclusters for ascorbic acid detection and fluorescence bacterial imaging - Wang, Baojuan; Fang, Jinxin; Tang, Huiliang; Lu, Shan; Chen, Yan; Yang, Xiaoqi; He, Yuezhen (Frontiers in Bioengineering and Biotechnology, 2023)
Protein-protected metal nanomaterials are becoming the most promising fluorescent nanomaterials for biosensing, bioimaging, and therapeutic applications due to their obvious fluorescent molecular properties, favorable biocompatibility and excellent physicochemical properties. Herein, we pioneeringly prepared a cellulase protected fluorescent gold nanoclusters (Cel-Au NCs) exhibiting red fluorescence under the excitation wavelength of 560 nm via a facile and green one-step method. Based on the fluorescence turn-off mechanism, the Cel-Au NCs were used as a biosensor for specificity determination of ascorbic acid (AA) at the emission of 680 nm, which exhibited satisfactory linearity over the range of 10–400 µM and the detection limit of 2.5 µM. Further, the actual sample application of the Au NCs was successfully established by evaluating AA in serum with good recoveries of 98.76%–104.83%. Additionally, the bacteria, including gram-positive bacteria (Bacillus subtilis and Staphylococcus aureus) and gram-negative bacteria (Escherichia coli), were obviously stained by Cel-Au NCs with strong red emission. Thereby, as dual-functional nanoclusters, the prepared Cel-Au NCs have been proven to be an excellent fluorescent bioprobe for the detection of AA and bacterial labeling in medical diagnosis and human health maintenance.